"Don´t do Land Reform: a simple theorem" - de Sousa, Miguel Rocha (2018)
We assess the general impact of land reforms on growth using human capital growth models due to Arrow (1962) - the main newness of the paper- after surveying the literature and building a typology. Thus, we conclude that land reform can yet been used as a modern tool to spur growth and development, but with our approach we can define the main limits and constraints that can block this growth. We conclude that a raise in undifferentiated wages after land reform leads to an unrecoverable society welfare loss; thus, yielding a lesson to political agents’ decision-makers elected after land reforms – wage raise land reform should not be used as an electoral motto.